Depletion of hepatic stellate cells inhibits hepatic steatosis in mice. Issue 10 (18th August 2022) - Kawahara, Akihiro; Kanno, Keishi; Yonezawa, Sayaka; Otani, Yuichiro; Kobayashi, Tomoki; Tazuma, Susumu; Ito, Masanori
Abstract: Background and Aim: Hepatic stellate cells (HSCs), the main source of extracellular matrix in hepatic fibrogenesis, produce various cytokines, growth factors, and morphogenetic proteins. Among these, several factors are known to promote hepatocyte lipid accumulation, suggesting that HSCs can be efficient therapeutic targets for non‐alcoholic steatohepatitis (NASH). This study aimed to investigate the effects of HSC depletion on the development of hepatic steatosis and fibrosis in a murine NASH model. Methods: C57BL/6 mice were treated with gliotoxin (GTX), an apoptosis inducer of activated HSCs under the feeding of a choline‐deficient l ‐amino acid‐defined high‐fat diet for 4 weeks. For in vitro study, Hc3716 cells, immortalized human hepatocytes, were treated with fatty acids in the presence or absence of LX2, immortalized HSCs. Results: Choline‐deficient l ‐amino acid‐defined high‐fat diet increased pronounced hepatic steatosis, which was attenuated by GTX treatment, together with a reduction in the number of activated HSCs. This change was associated with the downregulation of the peroxisome proliferator‐activated receptor gamma (PPARγ) and its downstream genes, including adipocyte protein 2, cluster of differentiation 36 (CD36), and fatty acid transport protein 1, all of which increase the fatty acid uptake into hepatocytes. As expected, GTX treatment improved hepatic fibrosis. Co‐culture of hepatocytes with HSCs enhanced intracellular lipid accumulation, together with the upregulation of PPARγ and CD36 protein expressions. Conclusions: In addition to the improvement in hepatic fibrogenesis, depletion of HSCs had a favorable effect on hepatic lipid metabolism in a mouse NASH model, suggesting that HSCs are potentially efficient targets for the treatment of NASH.